Early Detection of Alterations in the Resonance Frequency Assessment of Oral Implant Stability on Various Bone Types: A Clinical Study - (:unkn) unknown (ALLEN PRESS INC, 2011)
This study was undertaken to evaluate the relation between bone quality and alterations of implant stability quotient values measured during the initial phase of healing. Nineteen patients treated with 106 implants were included in the current study. The mean bone density of the implant recipient area was measured using Simplant 11 software incorporated in the computerized tomography (CT) machine. Mean bone density measurements were recorded in Hounsfield units. The implant recipient sites were subdivided into 5 groups according to bone quality. The numbers of the structures on the recipient site belonging to D1 and D5 types showed no statistical significance and were excluded. Standard 2-stage surgical technique was utilized to prepare the surgical sites. The implant stability quotient (ISQ) value at implant placement was recorded and did not influence the treatment procedure. The ISQ was measured by an Osstell instrument. The ISQ was further registered on the 21st and 60th days. SPSS statistical software was used for the statistical analysis. In comparison with the time of insertion, the mean values of the ISQ were decreasing for the first 21 days. However, on subsequent days, the ISQ values of all bone types have increased and on the 60th day reached the values recorded at the time of insertion. Analysis of the relation between changes in stability and bone type does not reveal statistical significance. With knowledge of the current clinical study, it can be concluded that bone quality in the recipient bone site does not effect changes in implant stability at the early stages of the osseointegration process.
Keywords: bone quality; computerized tomography; implant stability; resonance frequency analysis; Simplant; COMPUTERIZED-TOMOGRAPHY VALUES; TITANIUM IMPLANTS; INITIAL STABILITY; CUTTING TORQUE; PLACEMENT; MAXILLARY; INTERFACE; INSERTION; STRENGTH; SURGERY